Comprehensive analysis of acute flaccid paralysis with and without myelitis in Taiwanese children - Chien-Heng Lin; Ru-Huei Fu; I-Ching Chou; Yu-Tzu Chang; Syuan-Yu Hong (Italian Journal of Pediatrics)
Abstract Background Acute flaccid paralysis (AFP) is a clinical syndrome marked by the sudden onset of muscle weakness or paralysis, requiring immediate medical intervention due to its potential for significant morbidity and mortality. Despite extensive studies on AFP, comparative analyses between cases with myelitis (M-AFP) and non-myelitis (NM-AFP) remain scarce. This study seeks to address this gap by analyzing demographic, clinical, and etiological distinctions between these groups. Methods A retrospective study was conducted on 39 pediatric AFP patients diagnosed between 2012 and 2021. Participants were categorized into M-AFP (n = 22) and NM-AFP (n = 17) groups based on clinical symptoms and diagnostic imaging. Demographic and clinical characteristics, laboratory findings, and underlying causes were analyzed to identify differences between the groups. Statistical methods were employed to assess significance. Results Significant clinical differences were observed: limb numbness was more prevalent in M-AFP, while myalgia was more common in NM-AFP. Elevated cerebrospinal fluid white blood cell (CSF WBC) counts were noted in M-AFP cases, though the difference was not statistically significant. Etiologies of M-AFP included multiple sclerosis and enterovirus infections, while NM-AFP involved polymyositis, Guillain-Barré syndrome, and hypokalemic periodic paralysis. Conclusions This study highlights the distinct clinical and etiological profiles of M-AFP and NM-AFP, emphasizing the need for tailored diagnostic strategies to enhance outcomes in pediatric patients.